СҮЎРЕТЛЕЎ ӨНЕРИНДЕ КОМПОЗИЦИЯ НЫЗАМЛЫЛЫҚЛАРЫН ОҚЫТЫЎДЫҢ ДИДАКТИКАЛЫҚ ТИЙКАРЛАРЫ - Каипов, Н. (FAN va JAMIYAT, 2018)
The article deals with the information about the importance and basic regularities of the composition in teaching the subject «Graphic arts». The author of the work describes the peculiarities of the composition, and offers to use them at the lessons in Graphic arts. He also studies the types and regularities of the composition and their use for the efficient teaching of Graphic arts.